Efeito da temperatura, do grau de trofia e do surfactante Dodecil Sulfato de Sódio nos crescimentos de Egeria densa (Planch) e de Chara sp. (Linnaeus) - Wanderley, Emmanuelle Leite (2020)
There is growing concern about the ecological impacts caused by human actions. We can mention the use of surfactants, where their presence in the aquatic ecosystem affects the quality of the water, and in addition to this we have the increase in water temperature, as a consequence of global warming, which determines the speed of the metabolic processes in the aquatic biota. In this context, this study evaluated the growth and physiological responses of two aquatic macrophytes (Egeria densa and Chara sp.) Under the effect of two concentrations (0.5 and 8.0 mg / L) of the sodium dodecyl sulfate surfactant (DSS), at two temperatures (25 and 27 ºC) and in eutrophic and oligotrophic growth media. The accumulated length, the growth constant (µ), the daily growth rate, the temperature coefficient (Q10), the doubling time (td), the number, contributions and the emergence time of the shoots were evaluated. The physiological analyzes of photosynthetic pigments (chlorophyll-a, chlorophyll-b, carotenoid) and antioxidants (anthocyanin and flavonoid) were carried out on the fresh biomass of Chara sp. and E. densa. Significant differences in growth (p < 0.0001) between the different treatments (control and DSS) were identified for both macrophytes. The increase of 2 ºC promoted greater accumulated growth in E. densa in eutrophic medium. For Chara sp. the thermal variation of 2 ºC, did not alter its accumulated growth in eutrophic medium. Plants grown in the medium enriched with nutrients and with the presence of DSS developed better when compared to the oligotrophic medium. The highest growth constant (µ) for Chara sp. occurred at 25 ° C and for E. densa at 27 ° C, both in eutrophic medium. Regarding the doubling time (dt), the highest was registered for E. densa, in the treatments with DSS, at 25 ºC (eutrophic). Q10 was higher (6.36) between the eutrophic medium temperatures for E. densa. For Chara sp., Q10 was 1.2 and 1.28 in the eutrophic and oligotrophic media, respectively. The treatments at 25 and 27 ºC (eutrophic) were responsible for the largest number and contributions of shoots in Chara sp. and E. densa, respectively. Chara sp. presented a continuous process of formation and loss of shoots; the number of sprouts and their contributions in relation to the growth medium and temperature were significant. The time of emergence varies between treatments, and for E. densa the variation occurred between 7 to 27 days, and for Chara sp., the period was between 3 and 7 days. Physiologically, the plants adapted to the presence of the DSS; variations in the concentrations of photosynthetic pigments and antioxidants were observed, with growth in oligotrophic medium (25 and 27 ºC), with the highest concentrations of pigments and antioxidants in both macrophytes. These results showed that the presence of DSS, combined with temperature and culture medium, influence the growth parameters of E. densa and Chara sp., without causing early senescence and consequent death of these species. There was adaptation, of both species, in relation to the variations of the possible DSS interferents, temperature and degree of trophic state of the medium in the growth.